Navigating the Genetic Frontier: Establishing Genetic Clinics for Comprehensive Hereditary Cancer Management in Resource-Limited Settings - Akhil Kapoor; Ankita Rungta Kapoor; Archi Rungta; Bal Krishna Mishra; Anuj Gupta; Bipinesh Sansar; Amit Kumar; Zachariah Chowdhury; Shashikant Patne; Satyajit Pradhan; Rajiv Sarin (Indian Journal of Medical and Paediatric Oncology)
This review article explores the vital role of genetic clinics in the management of hereditary cancers, emphasizing their significance in early detection, tailored treatment, and family screening. It presents analysis of the prevalence of hereditary cancers in India, including breast, ovarian, prostate, colon, and kidney cancers, stressing the necessity for effective genetic testing and counseling services.